A Survey of the Mussels (Unionidae) of the Upper Tennessee River- 1978 - W. Jeffrey Pardue (Hello World!, 1981)
This account of the mussels of the upper Tennessee River in-cludes portions of the mainstream Tennessee River from Walden Gorge, west of Chattanooga, Tennessee, to Fort Loudoun Dam, south of Knoxville, Tennessee. Collections were made downstream from each of the three mainstream dams (Fort Loudoun; Watts Bar, Chickamauga) for varying distances depending on the quality of the substrate. Eighty-six stations were sampled which yielded a total of only 21 extant species as compared to 57 species reported by Ortmann (1918). Slight changes in faunal composition have occurred since Scruggs' survey (1960). Most notable of the changes are (1) invasion of typical post-impoundment species (6 of the 21 extant species) and (2) the occurrence of Dromus dromas (lea, 1834), a Cumberlandain species not reported from the Tennessee River since Ortmann (1918).